Reducing inequities in maternal and child health in rural Guatemala through the CBIO+ Approach of Curamericas: 4. Nutrition-related activities and changes in childhood stunting, wasting, and underweight - Henry B. Perry; Ira Stollak; Ramiro Llanque; Stanley Blanco; Elizabeth Jordan-Bell; Alexis Shindhelm; Carey C. Westgate; Andrew Herrera; Mario Valdez (BMC, 2023)
Abstract Background This is the fourth paper in our supplement on improving the health and well-being ﻿of rural indigenous Maya mothers and children in the Western Highlands of Guatemala, where the prevalence of stunting is the highest in Latin America and among the highest in the world. Reducing childhood undernutrition was one of the objectives of the Maternal and Child Health Project, 2011-2015, implemented by Curamericas/Guatemala. The implementation research portion of the Project attempted to determine if there were greater improvements in childhood nutritional status in the Project Area than in comparison areas and whether or not a dose-response effect was present in terms of a greater improvement in the Project Area with a longer duration of interventions.  Methods The Project provided nutrition-related messages to mothers of young children, cooking sessions using locally available nutritious foods, a lipid-based nutrient supplement (Nutributter®) for a short period of time (4 months)﻿, anti-helminthic medication, and repeated growth monitoring and nutrition counseling. Measures of height and weight for calculating the prevalence of underweight, stunting, and wasting in under-2 children were analyzed and compared with the anthropometric data for children in the rural areas of the Northwestern Region and in the Western Highlands of Guatemala. Results The prevalence of stunting declined in Area A from 74.5% in September 2012 to 39.5% in June 2015. Area A comprised approximately one-half of the Project Area and was the geographic area with the greatest intensity and duration of nutrition-related Project interventions. Minimal improvements in stunting were observed in the Northwestern Region, which served as a comparison area. Improvements in multiple output and outcome indicators associated with nutritional status were also observed in Areas A and B: infant and young child feeding practices, routine growth monitoring and counseling, and household practices for the prevention and treatment of diarrhea. Conclusion The Project Area in which Curamericas/Guatemala implemented the CBIO+ Approach experienced a reduction in the prevalence of stunting and other measures of undernutrition in under-2 children. Given the burden of undernutrition in Guatemala and other parts of the world, this approach merits broader application and further evaluation.